The role of women in history according to textbooks images. Comparison of textbooks published during LOE and LOMCE - Juan Carlos BEL MARTÍNEZ (Ediciones Universidad de Salamanca, 2017)
This paper focuses on the study of the role of women and its representation in the images of the textbooks of Environmental Knowledge and Social Sciences subjects, specifically in History topics. Textbooks can give us an overview of how women are presented in the historical discourse carried from Primary Education, and through their analysis we can see if it has or not an androcentric bias. Therefrom it's developed an analysis and a comparison of the data between volumes of both last education laws implemented in Spain (LOE and LOMCE).